Peningkatan Kemampuan Kader Posyandu Gizi melalui Pendampingan dan Edukasi Akuntansi - Effendi, Bahtiar (Ilin Institute, 2021)
This community service activity aims to provide education and assistance for the Cadre of Posyandu Nanas (Nutrition), Mekarwangi Village, Tangerang Regency, by providing adequate understanding of effective bookkeeping (accounting) practices and the introduction of financial accounting standards for non-profit organizations (PSAK 45). The implementation of the third PKM activity in the Odd semester of 2021-2022 has been completed. Based on these activities, the cadres of the Nanas Posyandu (Nutrition) were quite assisted in the bookkeeping process which had been considered difficult because of their educational competence, which was the majority of elementary and junior high schools so that their competence needed to be improved again so that the Posyandu accounting (accounting) practice could run effectively and increase the timeliness of reporting. bookkeeping to the Midwife and the Mekarwangi Village Health Center.